Public administration for green port development strategy - Hoang Oanh, Truong Thi; Hoang Thao, Doan Thi; Long, Tran Duc; Sanh, Tran Van; Minh Vu, Pham Le (Tạp chí Khoa học Công nghệ Giao Thông Vận Tải, 2024)
The maritime sector is crucial for socioeconomic development and safeguarding the internal security and defense of the country. Ecosystems may be harmed by dredging and ship activities at ports. Services at seaports for transporting passengers and cargo are believed to be responsible for releasing approximately 20% of worldwide waste into the sea. Increased port activities heighten the risk of pollution, leading to a substantial adverse effect on the ecosystem. Thus, the goal is to prevent environmental contamination and construct sustainable seaports to balance environmental conservation and economic growth. However, there is no universal approach for constructing green ports globally, as it varies based on the specific circumstances of each seaport. A comprehensive set of documents and legislation aimed at reducing pollution in permeable ecosystems in Vietnam has been assembled, especially the Green Port Development Project and recommendations have been provided following a comparison with worldwide case studies. Additional improvements are needed in green concession policies, minimizing ship and inland transport idling and terminal waiting times, and carbon capture and storage.